Struktur komunitas ekosistem mangrove di kawasan pesisir Sidangoli Kabupaten Halmahera Barat, Maluku Utara - Nebuchadnezzar Akbar; Abdurrachman Baksir; Irmalita Tahir (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2015)
Abstract. Mangroves is important ecosystem in coastal. However, multiple destructive activities to cause reduced mangrove area. The information about area and criteria of mangrove in Sidangoli coastal area, had been doing, however information ecology mangrove unexplored. This information is required to plan better conservation strategy of mangrove. The study was conducted to infer the ecology of mangrove in the Sidangoli coastal of west halmahera regency, North Mollucas. A total of location diveded by four and perform in November 2014. Mangrove sampling, done by the